Characterization of Ionization Phenomena in Soils Under Fast Impulses - Nor, N.M.; Haddad, A.; Griffiths, H. (2006)
Protective devices such as spark gaps and surge arresters are used to divert surges to earth. It is, therefore, necessary that earthing systems are designed with a low-magnitude earth impedance value so that the overvoltage protection devices can divert high fault currents effectively to earth for all types of fault. Power frequency characterization of earthing systems is extensively researched and fairly well understood. However, the behavior of such systems under transient conditions is still not fully clarified.